Visceral politics: imaginaries of power in South India - Arumugam, Indira (Cambridge University Press, 2025)
"When the gods stop roaming across the lands and encountering their devotees in person - what does this reveal about ongoing political upheavals? What does the insouciant trespassing of crows into human houses convey about how different kinds of kin should behave? How can offering sacrifice be tantamount to building and powering a polity? This book delineates the dynamics of a micro-polity as embodied in and made vital through the kinship, rituals, feuds, myths, and everyday lives of people in a Tamil Nadu village. Framed by caste exclusions and women's marginalization and substantiated by relations of lineage kinship, the constitutive premises of this hierarchical polity also feed into a contemporary electoral politics that claims to be more inclusive and egalitarian. Eviscerating a body politic, this book lays bare the tissues that constitute and the capillaries that nourish the political. Power structures, political interactions, and ideals are made flesh in and animated in the persons of kinsmen, the territories in which they co-reside, and the bodies of sacrificial animals. It explores how ordinary people in the process of living their everyday lives also theorize for themselves the construction of realms and the establishment of reign. At the heart of this exploration is viscerality. Exploiting the rawness, elementality, and vitality underpinning the visceral as well as the ultimate mystery at its heart, this book goes beyond politics as ideology, interest, or instrumentality to interrogate just how it moves people and gets them in its grip"-- Provided by publisher